The Influence of Motivation, Leadership and Perceived Workload as Intervening on Teacher Commitment - Robby Anzil Firdaus; Dian Purnamasari; Stefy Falentino Akuba (Journal of Educational Science and Technology (EST), 2019)
At various schools, there are problems related to teacher commitment for carrying out their work. In schools that were the object in this study, problems related to low teacher commitment can be seen in the exit interview process when teachers submit resignations. This study objective is to look for the influence of leadership, motivation and perceived workload on teacher commitment at the school. This research was conducted at an Islamic school in the southern city of Tangerang.The method of sampling is census of 61 permanent teachers under the organization. The analizing method is SEM  using SmartPLStm software. The result from SEM intrepertation shows there is significant influence on leadership and perceived workload, motivation and commitment as well as perceived workload and commitment. Leadership can also influence commitment through mediating perceived workload. Base on the results, the conclusios are, to increase teacher’s commitment, we need to see the leadership style of the principles of the school (as direct supervisor), gave a good insight for their perceived workload so that they do not feel overwhelming. Thus their commitment will also increasing.